A Technical Note on the Approach to the Fifth Plan of India 1974-79 - Planning Commission (Planning Commission, 1973)
To facilitate the task of drawing up the “approach” to the Fifth Plan, Perspective Planning Division of the Planning Commission undertook a series of numerical exercises in close consultation with different Divisions of the Commission. The purpose of these exercises was to help the Commission in deciding on a rate and pattern of growth that would correspond to the overall objectives that the Commission had set to itself in regard to the formulation of the Fifth Plan. The nature of the calculation schemes adopted was basically determined by three factors: (a) the nature of the objectives to be realized; (b) the type and coverage of data currently available and (c) the nature of computing facility that could be utilized by the Commission. Arnone these factors,
Perspective Planning Division Planning Commission Government of India